SANITASI LINGKUNGAN DI KECAMATAN RUNGKUT - Lilis Sulistyorini; Soenarnatalina Melaniani (Jurnal Layanan Masyarakat (Journal of Public Services), 2018)
Surabaya as the capital of East Java Province still has unhealthy housing coverage conditions of 16.54%. Unhealthy housing conditions are influenced by several things, including due to knowledge factors or because of environmental conditions that are not possible. Community service activities in the form of training to the community about environmental sanitation in the Rungkut District aims to increase awareness of the application of environmental sanitation to the community. Efforts to train the community in the implementation of environmental sanitation in the community with PKK cadres and family heads so that conditions of goodand integrated environmental sanitation can be achieved in the community. The activities carried out were socialization to the community regarding the importance of maintaining environmental sanitation on the first day and socialization of the construction of latrines and healthy septic tanks on the second day. The results of the activity showed the participants were enthusiastic throughout the event, there were 3 questions in the Question and Answer session as a form of enthusiasm of the participants. The results of the pre-test and posttestshowed an increase in the score of participants. The socialization of latrine construction and healthy septic tanks went smoothly, some participants showed enthusiasm to build latrines and septic tanks by asking for the number of latrine credit providers. A week after the socialization was carried out the construction of a septic tank in the house of one of the less fortunate residents, with funding from the community service team and the construction of septic tanks in 3 houses of interest at the time of the socialization, at an independent cost. Itis expected to be able to do similar activities in other locations so that environmental sanitation in Surabaya, especially regarding the ownership of septic tanks in Surabaya can be even better.AbstrakSurabaya sebagai ibukota Provinsi Jawa Timur masih memiliki kondisi cakupan rumah yang tidak sehat sebesar 16,54%. Kondisi rumah yang tidak sehat dipengaruhi oleh beberapa hal, antara lain karena faktor pengetahuan maupun karena kondisi lingkungan yang tidak memungkinkan. Kegiatan pengabdian masyarakat berupa pelatihan kepada masyarakat tentang sanitasi lingkungan di Kecamatan Rungkut bertujuan untuk meningkatkan kesadaran penerapan sanitasi lingkungan pada masyarakat. Upaya melatih masyarakat dalam penerapan sanitasi lingkungan di masyarakat dengan kader PKK dan Kepala Keluarga sehingga dapat tercapai kondisi sanitasi lingkungan yang baik serta terpadu di masyarakat. Kegiatan yang dilakukan yakni sosialisasi kepada masyarakat terkait pentingnya menjaga sanitasi lingkungan pada hari pertama serta sosialisasi tentang pembangunan jamban dan septic tank yang sehat pada hari kedua. Hasil kegiatan menunjukkan para peserta kegiatan tampak antusias sepanjang acara, terdapat 3 pertanyaan pada sesi Tanya-Jawab sebagai bentuk antusiasme peserta. Hasil pre-test dan post-test menunjukkan terdapat peningkatan skor peserta. Sosialisasi pembangunan jamban dan septic tank sehat berjalan dengan lancar, beberapa peserta menunjukkan antusiasme untuk membangun jamban dan septic tank dengan menanyakan nomor penyedia kredit jamban. Seminggu setelah sosialisasi dilakukan pembangunan septic tank di rumah salah satu warga yang kurang mampu, dengan dana bantuan dari tim pengabdian masyarakat serta terdapat pula pembangunan septic tank di 3 rumah warga yang tertarik pada saat sosialisasi dilakukan, dengan biaya mandiri. Diharapkan dapat dilakukan kegiatan sejenis di lokasi lain agar sanitasi lingkungan di Surabaya, terutama terkait kepemilikan septic tank di Surabaya dapat lebih baik lagi.